The Whole of Human Relations: Learning More than Art, More than Making (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2015)
The article discusses a six-week long experimental, inter-media art course organized at the University of Saskatchewan in partnership with Saskatoon Tribal Council. This community-engaged teaching initiative, Project Charter: Call for Artisans, The Child Taken, provided art students in a senior interdisciplinary studio course with an opportunity to partake in the creation of an art commission commemorating Indian Residential Schools. Focusing on various dimensions of the project the article discusses the professional and experiential learning generated in response to the partnership request from the Saskatoon Tribal Council and highlights project undertakings as best practices in community-engaged pedagogy.